Pengaruh Free Cash Flow dan Trading Volume Activity terhadap Return Saham pada Perusahaan Farmasi (Bursa Efek Indonesia Periode 2018 – 2022) - Maharani, Septia Putri; Situngkir, Tiar Lina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to see how trading volume activity and free cash flow have an impact on stock returns for pharmaceutical companies (Indonesia Stock Exchange Period 2018–2022). This research utilizes a quantitative approach that uses a descriptive and verification approach. The research samples were eight pharmaceutical companies listed on the Indonesia Stock Exchange from 2018 to 2022. A total of 40 data were collected using a purposive sampling technique for 5 years of observation. Descriptive and verification analyzes were performed, including classical assumptions (normality, heteroscedasticity, autocorrelation and multicollinearity), multiple linear regression analysis, t-test and f-test. Data processing was carried out using SPSS 26. The results of testing the data showed that free cash flow and trading volume activity partially affected stock returns. then simultaneously stock returns are influenced by free cash flow and trading volume activity. Keywords: Free Cash Flow, Trading Volume Activity, Stock Returns.